Modelling of Data Warehouse on Food Distribution Center and Reserves in the Ministry of Agriculture - Putra, Edi Purnomo; Fifilia, Fifilia; Christian, Lay; Sudarma, Hantze (Bina Nusantara University, 2015)
The purpose of this study is to perform database’s planning that supports Prototype Modeling Data Warehouse in the Ministry of Agriculture, especially in the Distribution Center and Reserves in the field of distribution, reserve and price. With the prototype of Data Warehouse, the process of data analysis anddecision-making process by the top management will be easier and more accurate. Research’s method used was data collection and design method. Data warehouse’s design method was done by using Kimball’s nine stepsmethodology. Database design was done by using the ERD (Entity Relationship Diagram) and activity diagram. The data used for the analysis was obtained from an interview with the head of Distribution, Reserve and Food Price. The results obtained through the analysis incorporated into the Data Warehouse Prototype have been designed to support decision-making. To conclude, Prototype Data Warehouse facilitates the analysis of data, the searching of history data and decision-making by the top management.